The Role of the School Private Development in Improving the Performance of Integrated PAUD Posyandu Teachers - Wijayanti, Erlia; Arafat, Yasir; Rosani, Meilia (Journal of Social Work and Science Education, 2023)
This study aims to describe the role of school principals in improving the performance of PAUD Posyandu teachers in Kec. Penukal Kab. Pali. The research was carried out at the integrated Kec. Penukal Early Childhood Health Center with the address of PU Village, Babat Dusun II Village, Penukal District, Penukal District, Abab Lematang Ilir. The research was carried out from February to April 2023. Data and information were collected by researchers while in the field by obtaining direct surveys. The documentation from primary and secondary sources and used to fulfill research requirements regarding the benefits and objectives of the research. The results of the research show that the results of the survey and documents that were carried out at the time of the research were quality improvement, guidance for school principals and supporting facilities and infrastructure in improving teacher performance in PAUD Posyandu.